STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN ETOS KERJA GURU DI PAUD AMAR LAMPUNG - Amin Asiah (UNISAN JURNAL, 2024)
The examination means to decide the hard working attitude of Islamic Strict Training (PAI) educators at PAUD Amar Lampung and the job of the vital’s administration in further developing the hard working attitude of PAI educators at PAUD Amar Lampung. The examination strategy utilized is subjective by deciphering a phenomenological point of view, in particular the way in which a scientist can comprehend and value the initiative of the school chief in further developing the hard working attitude of PAI educators. In view of the aftereffects of examination led in regards to the Position of authority of School Administrators in Further developing the Hard working attitude of Amar Lampung PAUD Educators, the accompanying ends were acquired: The Job of Head Administration in expanding work resolve. Thus, above all else, the chief should be excited about working despite the fact that he has numerous obligations. With this, it is trusted that great collaboration will be laid out to acknowledge cutthroat training at PAUD Amar Lampung. The head, staff and educator chamber have given their trust so the neighborhood local area can believe the nature of this school by entrusting their youngsters to get instruction at this school. The school head’s endeavors presumed that the educator’s work discipline here was supposed to be great, in light of the fact that the chief’s demeanor was consistently dependable in his participation. The chief attempts to make extra energy with valuable exercises. Along these lines, instructors, staff and understudies become industrious, however their discipline needs to keep on being gotten to the next level. The progressive, groundbreaking and facilitative systems carried out by the Head of PAUD Amar Lampung have suggestions for the hard working attitude of PAI educators, including: 1) high excitement, 2) clean ethics, 3) trustworthiness, 4) responsibility, 5) istiqomah, 6 ) discipline, 7) steady and bold in confronting difficulties, 8) self-assured, 9) imaginative, and 10) capable